2007
DOI: 10.1111/j.1745-3992.2007.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Subscores Based on Classical Test Theory: To Report or Not to Report

Abstract: There is an increasing interest in reporting subscores, both at examinee level and at aggregate levels. However, it is important to ensure reasonable subscore performance in terms of high reliability and validity to minimize incorrect instructional and remediation decisions. This article employs a statistical measure based on classical test theory that is conceptually similar to the test reliability measure and can be used to determine when subscores have any added value over total scores. The usefulness of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 16 publications
3
80
0
Order By: Relevance
“…More recently, Haberman (2005Haberman ( , 2007Haberman, Sinharay, & Puhan, 2006;Sinharay, Haberman, & Puhan, 2007) found that reliability-based analysis is helpful in informing the decision of reporting subscores. His approach compares the root mean square error (RMSE) of the true subscore when it is predicted (or approximated) by the observed subscale score, the observed total test score, and the two scores conjointly.…”
Section: Methods and Analysesmentioning
confidence: 99%
“…More recently, Haberman (2005Haberman ( , 2007Haberman, Sinharay, & Puhan, 2006;Sinharay, Haberman, & Puhan, 2007) found that reliability-based analysis is helpful in informing the decision of reporting subscores. His approach compares the root mean square error (RMSE) of the true subscore when it is predicted (or approximated) by the observed subscale score, the observed total test score, and the two scores conjointly.…”
Section: Methods and Analysesmentioning
confidence: 99%
“…The approach of Haberman (2008) (Haberman, 2008). Sinharay, Haberman, and Puhan (2007) discussed why this strategy is reasonable and how it ensures that a section score satisfies professional standards. A larger value of x PRMSE for a TOEFL section means than the corresponding TOEFL section score does a better job than the TOEFL total score of predicting the corresponding true section score.…”
Section: Analysesmentioning
confidence: 99%
“…If we are confident that we are successfully measuring 'clinical skills' only at the whole-OSCE level, a narrow psychometric viewpoint might argue that pass/fail decisions must be made based on this. Making decisions that rest, to an extent, on subsets of stations where decisions are subject to greater, possibly unacceptable, error could be construed as less robust (Sinharay, Haberman, & Puhan, 2007;Sinharay, Puhan, & Haberman, 2011).…”
Section: Station Level Effectsmentioning
confidence: 99%